A Commentary: the Inadmissibility of Non-Indonesian Citizens in Judicial Review before the Indonesian Constitutional Court - Mahendra, Bayu (Constitutional Review, 2017)
The Constitutional Court of Indonesia, in its judgment No 2-3/PUUâV/2007, ruled that non-Indonesian citizens have no legal standing to file judicial review before the Court. In determining the legal standing, the Court rejected applicantsâ constitutional loss which should actually serve as the substantial examination in judicial review but rather addressed this question on the basis of applicantâs citizenship. This inadmissibility ruling, however, raises question on what legal standing actually mean in the context of judicial review. This paper reviews the Courtâs consideration in determining legal standing status and examines future legal consequences of such reasoning. By revisiting the substance of legal standing and judicial review derived from the 1945 Constitution, relevant Statutes, Courtâs practices and case law, as well as the dissenting opinion of the judges in this case, it is found that the Court overruled the substance to procedural examination on the basis of citizenship and therefore failed to address the actual question of legal standing. This paper concludes that the Courtâs reasoning has abandoned the constitutional loss as the very substance of legal standing and to which amounts to immunity of legal standing provision from a judicial review. Consequently, non-Indonesian citizens will never be recognized in judicial review mechanism before the Indonesian Constitutional Court.